Integrasi Prinsip Sakinah-Mawaddah-Rahmah dalam Pembinaan Keluarga Muslim Kontemporer: Kajian Tematik Al-Qur’an terhadap Fondasi Ketahanan Keluarga - M. Ridho Firdaus; Ilyas Husti; Hidayatullah Ismail (JURNAL ILMIAH NUSANTARA, 2026)
The concepts of Sakīnah, Mawaddah, wa Raḥmah constitute a spiritual and emotional trilogy that the Qur'an proclaims as the fundamental goal of marriage (QS. Ar-Rum: 21). This study aims to analyze thematically (maudhū'ī) the integration of these three principles as the main foundation for the development and resilience of Muslim families in the contemporary era. Through a qualitative approach with literature study and thematic interpretation, it was found that Sakīnah (inner peace) functions as a spiritual foundation; Mawaddah (active, passionate love) as the driving force of the relationship; and Raḥmah (loving kindness that is ready to sacrifice) as a safety net and sustainability. The integration of these three elements provides an ideal model for contemporary Muslim families to face challenges such as digital disruption, changing gender roles, and economic pressures. The results of the study confirm that family resilience does not only depend on material aspects, but primarily on the quality of transcendental relationships based on Qur'anic values.